Framing of ‘terrorism’ issues in Indonesia: a study of two Malaysian mainstream newspapers / Dafrizal Samsudin and Faridah Ibrahim - Samsudin, Dafrizal; Ibrahim, Faridah (CMIWS and UiTM Press, 2010)
Indonesia is one of the ASEAN countries that is always struggling with terrorism issues. It has also been the focus of the international news media where terrorism issues are concerned. On 17th July 2009, once again Indonesia is traumatised yet with another terrorism incident with the bombing of JW Marriot and Ritz-Carlton Hotel in Jakarta. This time Malaysia also becomes a major focus in the international agenda. This is because the prosecution of Nordin Mat Top, a Malaysian citizen who is said to mastermind a series of bombings in Indonesia, is widely discussed in the mass media, both in Malaysia and Indonesia and also at the international level. In this situation how would the Malaysian mainstream media report the story on terrorism in a neighbouring country, when the terrorist himself is from Malaysia? Hence, it is interesting to look at how Malaysia writes about terrorism news in Indonesia especially with this case in point. Furthermore, with a heavy reliance on the international news agencies for international news coverage, will Malaysia adopt the same news frame as created by the international agencies when writing about terrorism issues or will the Malaysian media create their own news frames in dealing with terrorism issues in Indonesia. The purpose of this study is to identify whether Malaysian mainstream media, specifically Utusan Malaysia and The New Straits Times, with different news orientation, language preferences and editorial policies, create their own news frames or subscribe to the frames created by the international news agencies in reporting terrorism issues in Indonesia.